The Cambridge Companion to British Romanticism / Ed. - Curran, Stuart (Cambridge : Cambridge University Press, 2010)
"This new edition of The Cambridge Companion to British Romanticism has been fully revised and updated and includes two wholly new essays, one on recent developments in the field, and one on the rapidly expanding publishing industry of this period. It also features a comprehensive chronology and a fully up-to-date guide to further reading. For the past decade and more the Companion has been a much-admired and widely-used account of the phenomenon of British Romanticism that has inspired students to look at Romantic literature from a variety of critical angles and approaches. In this new incarnation, the volume will continue to be a standard guide for students of Romantic literature and its contexts"--
Machine generated contents note: Preface Stuart Curran; Chronology; 1. Romanticism and the 'schools' of criticism and theory Jerrold E. Hogle; 2. Romanticism and Enlightenment Marshall Brown; 3. Poetry in an age of revolution P. M. S. Dawson; 4. German Romantic Idealism Peter Thorslev; 5. Romanticism and language William Keach; 6. Culture's medium: the role of the review Marilyn Butler; 7. Publishing and the provinces in Romantic-era Britain Stephen C. Behrendt; 8. Women readers, women writers Stuart Curran; 9. Romantic fiction Gary Kelly; 10. Romantic poetry: why and wherefore? Stuart Curran; 11. The sister arts in British Romanticism Morris Eaves; Guide to further reading; Index.
Keywords: English Literature -- History and Criticism; Romanticism